Age-dependent morbidity and mortality outcomes after surgical aortic valve replacement. (9th May 2018) - Hussain, Amjad I; Auensen, Andreas; Brunborg, Cathrine; Beitnes, Jan Otto; Gullestad, Lars; Pettersen, Kjell I
Abstract: OBJECTIVES: This study addressed the assumption of increased morbidity and mortality after surgical aortic valve replacement in patients older than 80 years with severe aortic stenosis. METHODS: This prospective study was performed in consecutive patients referred for aortic valve replacement. The age-dependent change in cognitive and physical function, quality of life and rehospitalization and complication rates during the following year and 5-year all-cause mortality were documented. RESULTS: A total of 351 patients underwent surgical aortic valve replacement. The death risk at 5 years was 10%, 20% and 34% in patients aged <70 years, 70–79 years and ≥80 years, respectively. Patients aged 70–79 years and ≥80 years had a hazard ratio of 1.88 [95% confidence interval (95% CI) 0.92–3.83, P  = 0.08] and 2.90 [95% CI 1.42–5.92, P  = 0.003] for mortality, respectively, when compared with patients aged <70 years. The length of stay and rehospitalization rate during the following year were similar between the groups. Patients ≥80 years of age experienced more delirium and infections, whereas the risks of new pacemaker, transient ischaemic attack (TIA) or stroke, myocardial infarction and heart failure were comparable between the age groups. All groups exhibited reduced New York Heart Association class, improved physical quality of life and unchanged mental scores without any clinically significant Mini Mental Status reduction. CONCLUSIONS: Elderly patients (≥80 years of age) have important gains in health measures and satisfactory 5-year survival with an acceptable complications rate during the year following surgery. Active respiratory mobilization and the removal of an indwelling urethra catheter can prevent adverse effects, and measures should be taken to prevent delirium and confusion in elderly patients. Clinical trial registration: clinicaltrials.gov (NCT 01794832).